Acrylamide monomers and polymers that contain phosphonate ions. (18th May 2015) - Hu, N.; Peralta, A.; Roy Choudhury, S.; Zhang, R.; Davis, R.M.; Riffle, J.S.
Abstract: Alkylacrylamide phosphonate monomers were synthesized by aza-Michael addition of an alkylamine onto the double bond of diethyl vinylphosphonate, then reaction with acryloyl chloride. Free radical copolymerization of n -butylacrylamide phosphonate with an acrylate-functional PEO macromonomer, then removal of the ethyl groups from the phosphonates led to poly( n -butylacrylamide phosphonic acid)- g -PEO copolymers. The copolymer comprising 56 wt% of the backbone and 44 wt% of PEO grafts was soluble in DMF, DMSO, methanol and water at pH 7.4. This copolymer formed aggregates in DMF and DMSO with only a few aggregates in methanol or water. Interaction of the phosphonic acid derivative (0.11 mmol) of n -butylacrylamide phosphonate with hydroxyapatite (0.15 or 0.30 mmol calcium ions) showed 80 and 95% extent of binding of the phosphonic acid whereas those values for acrylic acid were 47 and 64%. The hydrolytically stable polyacrylamide phosphonates with their excellent binding properties to hydroxyapatite make them potential candidates for adhesives. Graphical abstract: Highlights: Synthesized acrylamide phosphonate monomers using aza-Michael addition. Prepared poly(acrylamide phosphonate- g -ethylene oxide) copolymers. Evaluated binding of the acrylamide phosphonic acid monomer with hydroxyapatite.